(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Nowadays, in the field of image processing so many new technologies are found out and for various purposes such as filtering, edge smoothing, edge sharpening, zooming, enhancing, fusing, noise and blur removing . But these primitive and conventional methods bring some noises and halo artifacts with them as well as they need more time for processing. The algorithms used in these methods are very large and complicated. This method mainly focuses on filtering of images along with image enhancing, image fusion, haze removal and detail enhancement. Weighted Guided Image Filter uses two types of filtering algorithm: First is Global Filtering and second is Local Filtering. Therefore, it makes filtering process easy, less complicated and less time consuming.